Analisis Dosis Efektif Pada Pemeriksaan CT-SCAN Kepala Kontras di Instalasi Radiologi Rumah Sakit Surya Husadha Denpasar - Juniaty Teroci Mamun; Kadek Yuda Astina; A. A. Aris Diartama (USADA NUSANTARA : Jurnal Kesehatan Tradisional, 2024)
The effective dose is the dose on the CT-Scan that hits the patient's organs. The effective dose received by the patient should not exceed 3 standards that have been set both nationally and internationally. Nationally, the dose received by patients has been regulated in the Head of Bapeten Regulation on Diagnostic Reference Level (DRL). While internationally, the effective dose is regulated in the International Commission on Radiological Protection (IRCP). According to BAPETEN number 1211/K/V/2021 CTDIvol contrast head is 60mGy while DLP is 2500mGy.cm. The purpose of this study was to determine the amount of effective dose received by patients at the CT-Scan examination of the contrast head at the Radiology Installation of Surya Husadha Hospital Denpasar. The method used in this research is the quantitative method. Reference sources used in the preparation of this article include books, as well as articles in English and Indonesian scientific journals.